Factors Affecting the Effectiveness of Literary Text Perception - Vashchenko, Iryna; Lytvynenko, Olena (East European Journal of Psycholinguistics, 2014)
The issues related to perception and understanding of different texts, especially literary ones   are   of   interest   for   the   researchers,   who   represent   various   scientific   approaches   and  theories. Peculiarities   of   the   reader’s   work   with   the   text,   the   author’s   role   in   this   process,   mechanisms   and components   of perception and   understanding   of   textual   information   were   explored   by   experts   from various fields of science, such as:    psychology, linguistics, philosophy, sociology etc. The problem of text perception is connected with the issues of personal psychology, psychology of thinking, language and speech. Perception is a creative act of reflection the text image in the reader ’s mind. Furthermore, it is the  subjectivization of  the text  content. Thus, the text is  endowed  with communicative,  cognitive, informative, psychological and social characteristics which the reader has to realize. The peculiarity of such realization of textual information is determined not only by the content of the text, but also by the individual psychological characteristics of a person who perceives the information. Study of properties  and manifestations, which can influence the process of literary text perception, opens up broad prospects not only to psychology, but also to a range of other scientific fields and spheres of practical activity. The article may be of interest to psychologists, literary critics, educators, PR and marketing specialists, and other professionals interested in the problems of human interaction with the text. ReferencesGranik, G. (1979). Psichologicheskaja Model Processa Formirovanija Umennii[Psychological Model of the Formation of Skills]. Voprosy Psychologii, 18, 64–69.Kamenskaya, O. (1990). Text i Kommunikatsija [Text and Communication]. Moscow:Vysshaya Shkola.Leontyev, A. (2003). Osnovy Psiholingvistiki [Fundamentals of Psycholinguistics].Moscow: Smysl.Pashkovsky, V., Piotrovskaya, V., Piotrovsky, R. (2009). Psichiatrichescaja Lingvistica [ThePsychiatric Linguistics]. Moscow: Librocom.Rubo, I. (1998). Psichologicheskiy Analiz Strategii Chteniya Nauchnogo Texta[Psychological Analyses of the Strategies of Scientific Text Reading]. Moscow.